A longitudinal analysis of self-prescribed complementary and alternative medicine use by a nationally representative sample of 19, 783 Australian women, 2006–2010. Issue 5 (October 2015) - Bowe, Steven; Adams, Jon; Lui, Chi-Wai; Sibbritt, David
Highlights Approximately 3 in 4 young and mid-aged Australian women use self-prescribed CAM. Use of herbal medicine was higher in mid-aged women, compared to young women. There was a substantial increase over three years in the use of vitamins/minerals. There was a considerable decline over three years in use of aromatherapy oils.